2010
DOI: 10.1002/chem.200902624
|View full text |Cite
|
Sign up to set email alerts
|

Room‐Temperature Alkane Reactivity in Zeolites: An H/D Exchange Study

Abstract: As evidenced by H/D exchange with acidic zeolites, isoalkanes react readily at room temperature whereas linear alkanes do not. The observed regioselectivity of the exchange process demonstrates that the main factor controlling the reaction is not the accessibility to the acid sites, but the intrinsic reactivity of the alkane. The mechanism is best rationalized by classic organic chemistry involving carbocationic intermediates including the Markovnikov rule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…Combining the results of previous studies [11,32] and the actual ones we can draw the following conclusions. The first step [32] of the mechanism is most probably controlled by some very acidic sites of the zeolite, probably of superacid strength.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…Combining the results of previous studies [11,32] and the actual ones we can draw the following conclusions. The first step [32] of the mechanism is most probably controlled by some very acidic sites of the zeolite, probably of superacid strength.…”
Section: Resultsmentioning
confidence: 77%
“…To reach the conclusion that the critical intermediates are carbenium ions for the subsequent steps, the use of 2MP for the in situ H/D exchange was essential to lift the ambiguity associated to isobutane, which is too symmetrical, as demonstrated recently. [11] It is, therefore, demonstrated that carbenium is the intermediate entity controlling the rate-determining step. The activation energy found in this study is comparable to the isobutane H/D exchange found in Truitt et al studies [26,38] on H-Beta or HZSM5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7][8][9][10]13 NMR is a quantitative technique allowing direct determination of the relative concentration of the species contained in a sample, and absolute concentration using internal or external standards. Besides the reactant molecules, solid catalysts possess NMR active nuclei (isotopes with nuclear spin I a 0) being 29 Si, 27 Al, 31 P, 1 H, 13 C,. .…”
Section: In Situ Solid State Nmr Spectroscopymentioning
confidence: 99%
“…27,29 The activation mechanism of branched alkanes, especially isobutane, on Brønsted acid sites of solid catalysts at ambient or lower temperature is also controversial. 26,[30][31][32][33] In situ solid state 1 H NMR spectroscopy was used to study the H/D exchange of deuterated isobutane on zeolite H-ZSM-5 in the absence of impurities of alkenes. 26,30 The results are described in Fig.…”
Section: Activation Of Alkanes At Low Temperature: H/d Exchange Exper...mentioning
confidence: 99%